A microwave system based on a UWB microstrip antenna for non‐invasive in vitro measurement of glycemia in human blood: An experimental study. Issue 4 (15th February 2022) - El Hassani, Oumaima; Saadi, Adil
Abstract: The current study focuses on a non‐invasive microwave system based on a UWB antenna for blood glucose measurements in the frequency range of 1–4 GHz. Calculations of the minimal values of microwave reflection coefficient (S11 Min) corresponding to various blood glycemia, as well as comparisons to measured values using the Vector Network Analyzer Anritsu MS46121B, were the major findings of this study. The results were in good agreement, with a shift of less than 5%, demonstrating the effectiveness of our microwave method in detecting blood glycemia. To define an experimental approach between blood and dextrose solution, a comparative study in terms of slops in a linear approximation of both S11 Min and resonant frequency versus glucose concentration for the two mediums was interesting. The deviations in the results are less than 5% in the range of 1–2 GHz. However, it is not the case in the ranges of 2–3 GHz and 3–4 GHz since the two mediums show contrary behavior regarding S11 Min and resonant frequency. Consequently, D‐Solution might be used to simulate blood using our system for the investigation of glycemia only in the range of 1–2 GHz.